Performance Analysis of Convolutional Network System for Heart Disease Prediction - M. David, Julie; Sarika, S (International Journal of Computer Sciences and Engineering, 2021)
Heart is one of the major parts of human body, which maintains life line. It pumps the blood and supplies to all parts of the body. Heart disease prediction is significant work. Here we propose a Heart disease prediction model and is a hybrid intelligent system developed using classifier such as deep learning, feature extraction tools, and normalization methods. This intelligent system shows the high accuracy than the other datamining classifier. In this paper, the proposed model will help the medical field to reduces the cost and work load, and also ensures the accuracy of result. This System is very efficient and effective.